Improving Students' Reading Comprehension by Using SQ3R Method - AHMAD BAKHTIAR (Scope : Journal of English Language Teaching, 2018)
In this research, the writer  uses an action research. For collecting the data, the writer uses test and observation. The data sources of the research are the eleventh grade of  MA Mutmainah Bogor which consists of 38 students and an English Teacher  as the observer. Cycle I consists of planning, action, observation and reflection. Cycle II added by the revision of cycle I. Based on the results of the research, in  cycle I the percentage of students who achieved  Minimum Accomplishment Criteria (MAC) 75 is 63%. In other words, 24 students had achieved Minimum Accomplishment Criteria (MAC), while 14 students have not reached MAC. In cycle II, all of  students have reached Minimum Accomplishment Criteria (MAC). The result shows, in cycle II all of the students are able to comprehend  the text and to determain the main idea and reached Minimum Accomplishment Criteria (MAC) in  reading  it is 75. Thus, the hypothesis in this research is acceptable. It  means,  there is a significant  increasing in using SQ3R method  to improve the students’ reading comprehension at the eleventh grade of MA Mutmainah Bogor. Therefore, the research was discontinued on the second cycle.